Concentration of morpholine residues in major fruits and juices and its dietary exposure in China. Issue 1 (2nd January 2019) - Cao, Pei; Chen, Da-Wei; Liang, Jiang; Wu, Ping-Gu; Wen, Sheng; Wei, Jing; Liu, Si-Jie; Wu, Xi-Mei; Zhao, Yun-Feng; Xu, Hai-Bin
ABSTRACT: Morpholine is a common chemical used as emulsifier in the preparation of wax coatings for some fruit to help them remain fresh and protect against insects and fungal contamination. It has been reported that morpholine has acute toxic effects on rodents. In the present study, morpholine concentrations were analysed in fruits (citrus fruits, apples, strawberries and grapes) and juices (apple juice and orange juice) in order to determine dietary exposure among the Chinese population. A total of 732 fruit and juice samples were collected during 2015–2016, which covered major foods in China. Fruit and juice consumption data were taken from China National Nutrient and Health Survey (2002) and include data from 16, 407 fruit or juice consumers. It was found that mean dietary exposure to morpholine residues from fruits and/or juices for general Chinese consumers and children 2–6 years old were 0.42 and 1.24 µg/kg bw/day, respectively. The 97.5% intake in general Chinese consumers and children 2–6 years old were 2.25 and 6.90 µg/kg bw/day, respectively. The primary food sources of the morpholine dietary intake of general Chinese consumers were citrus fruits (57.4%) and apples (40.8%). These findings suggested that dietary exposure to morpholine in the Chinese population was lower than the acceptable daily intake of morpholine, and there are no health concerns.